2005
DOI: 10.1080/00207450590914365
|View full text |Cite
|
Sign up to set email alerts
|

Projected Color Slides as a Method for Mass Screening Test for Color Vision Deficiency (A Preliminary Study)

Abstract: This article compared the efficiency of the mass screening test with projected color slides in detecting color-blindness with the authentic classic method of Ishihara. The study was conducted in a randomly selected lecture room with 104 students aged between 19-25 years (median 21). Using Ishihara projected slides, performed mass screening test. Re-testing was done individually with printed Ishihara plates. Six male and one female with color-blindness were detected. The frequency of color-blindness was 13.6% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…The sensitivity and specificity of the online version of the Ishihara correlates with results by Gündogan et al 8 and Ganley et al 9 Although a limitation of this study is the relatively small sample size, the results of the study provide useful information for optometric practitioners and the general public on the use of online methods for screening colour deficiency. It is recommended that future research should include a larger, more representative sample, as well as consider the use of different types of monitors and the impact of lighting and screen resolution on online testing results.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The sensitivity and specificity of the online version of the Ishihara correlates with results by Gündogan et al 8 and Ganley et al 9 Although a limitation of this study is the relatively small sample size, the results of the study provide useful information for optometric practitioners and the general public on the use of online methods for screening colour deficiency. It is recommended that future research should include a larger, more representative sample, as well as consider the use of different types of monitors and the impact of lighting and screen resolution on online testing results.…”
Section: Discussionsupporting
confidence: 56%
“…Several studies have compared the Ishihara Pseudo-isochromatic plate test to modified electronic versions. Gündogan et al 8 compared the efficiency of projected colour slides in detecting colour deficiency, compared with the classic method of the Ishihara Pseudo-isochromatic plates. The authors concluded that using projected slides was an effective and timesaving method for detecting colour deficiency.…”
Section: Birchmentioning
confidence: 99%
See 1 more Smart Citation
“…Computergenerated pairs of tooth-shaped patches of color in computercontrolled color monitors provide an effective way of measuring human sensitivities to tooth color differences. 29 The ability to simulate protanopy and deuteranopy for the color matching process, coupled with the computer's inherent capacity to automate data collection in an efficient and highly repeatable way, may offer a new methodology to collect data for statistical evaluation of severe CVD effects on color matching abilities.…”
Section: Discussionmentioning
confidence: 99%
“…The Ishihara test has a long clinical history and high sensitivity and specificity (19,20). Some studies have reported that this test is the most effective method to ascertain red-green CVD (21,22). In this study, the test plates were displayed to the individuals at a distance of 75 cm in an appropriately illuminated room.…”
Section: Methodsmentioning
confidence: 99%